Pluralisme Agama dalam Tafsir Al-Misbah: Analisis terhadap Pemikiran Quraish Shihab pada Konteks Keindonesiaan - Rezwandi Rezwandi; Ahmad Fikri; Tasya Avanti Digdayani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study focuses on examining the concept of religious pluralism as contained in Quraish Shihab's monumental work Tafsir Al-Misbah, with particular emphasis on the significance of his thinking in the contemporary Indonesian landscape. As is widely known, Indonesia is a nation with extraordinary diversity in terms of religion and culture, and it constantly faces the challenge of maintaining social cohesion amid the potential for friction between religious communities. Tafsir Al-Misbah presents a perspective that promotes inclusiveness towards religious pluralism, based on the fundamental universal principles contained in the Qur'an, such as justice, empathy, and respect for diversity. This study implements a qualitative methodology through content analysis techniques on relevant arguments in Tafsir Al-Misbah, particularly those related to interfaith interaction. The results of this study show that: First, Quraish Shihab emphasises the importance of understanding pluralism as sunnatullah (God's decree) and the basis for creating a mutually respectful society. Second, Quraish Shihab's contextual interpretation refers to Indonesia's experience as a multireligious nation.